Peran Guru Sosiologi Dalam Upaya Mengembangkan Kecerdasan Emosional Siswa Di SMA Negeri 1 Tirtayasa - Himayati, Himayati; Widiyansyah, Subhan; Kuntari, Septi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The development of students' emotional intelligence at SMA Negeri 1 Tirtayasa is not yet completely perfect because there are still some students who are not yet able to recognize or manage their emotions, and there are even students who still behave unnaturally because they depend on how their friends treat them. This is motivated by several factors, especially broken homes, which in this case greatly influence the child's mental and emotional development process. The next factor is a family that is less harmonious, this can also affect the child's mental and emotional development process because the child will feel that he is not cared for enough so that the child looks for attention in the surrounding environment, even within the child there will definitely be feelings of anger towards other people because The child is jealous of his friend who lives in a perfect and harmonious family. In this research, the focus is on the role of sociology teachers in efforts to develop students' emotional intelligence at SMA Negeri 1 Tirtayasa. The teacher provides direction such as advice, guidance, and also a sense of security so that students feel safe when they want to tell what is happening inside them.